Ru-Ni bimetallic catalyst for selective hydrogenation of quinoline organic hydrogen storage carrier as well as preparation method and application of Ru-Ni bimetallic catalyst
By supporting the Ru-Ni bimetallic catalyst on the carbon nitride support, the existing catalysts have been solved, the problems of low activity, poor selectivity and short life in the hydrogenation reaction of quinoline organic hydrogen storage support are achieved, and a highly efficient, selective and cyclic stable hydrogenation reaction is achieved.
Patent Information
- Application Number
- CN202411644201.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-18
AI Technical Summary
In the hydrogenation reaction of quinoline organic hydrogen storage support, it is difficult to achieve high catalytic activity, selectivity and long cycle life at the same time, resulting in a short service life.
Using Ru-Ni bimetallic catalyst, the mass ratio of metal nanoparticles Ru and Ni is controlled to be 5: (1.5-2.5) by loading metal nanoparticles Ru and Ni on the carbon nitride support to achieve efficient selective hydrogenation of quinoline-based organic hydrogen storage support.
It realizes efficient hydrogenation of quinoline organic hydrogen storage support under solvent-free conditions, ensures the improvement of mass hydrogen storage density, the improvement of conversion rate and product selectivity, and significantly extends the cycle life of the catalyst.
Smart Images

Figure CN119503724A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a Ru-Ni bimetallic catalyst for selective hydrogenation of a quinoline organic hydrogen storage carrier, and a preparation method and application thereof. Background Art
[0002] Hydrogen plays an increasingly important role in the development of sustainable energy. It is a clean energy carrier that can be produced from renewable energy and used in various sectors such as transportation, industry and power generation. Hydrogen storage is a key issue in the development of the hydrogen economy. Among them, one of the most promising hydrogen storage and transportation technologies is the use of organic hydrogen storage carriers. Organic hydrogen storage technology is based on the chemical binding, transportation, storage and subsequent extraction of H2 at the location of use of H2 in organic molecules (such as aromatic compounds and N-heterocycles).
[0003] Although organic hydrogen storage technology has great application potential, it faces several scientific bottlenecks, including the need for efficient and durable catalysts, optimization of hydrogen storage capacity, and the kinetics of the hydrogenation process. Therefore, the development of hydrogenation catalysts with high catalytic activity, high selectivity, low cost, and good catalytic stability has become the key to the commercial application of N-heterocyclic organic hydrogen storage carriers.
[0004] Quinoline is an N-heterocyclic organic hydrogen storage carrier with an adjustable mass hydrogen storage density of 3-7.19%. Its physical and chemical properties are similar to those of petroleum. The mass hydrogen storage capacity of its fully hydrogenated product (DHQ) is 7.19wt.%, and the mass hydrogen storage capacity of its semi-hydrogenated product 1,2,3,4-tetrahydroquinoline (Py-THQ) is 3.0wt.%, which is a hydrogen storage carrier with great application prospects.
[0005] The catalysts reported so far for hydrogenation of quinoline organic hydrogen storage carriers cannot simultaneously achieve high catalytic activity and high selectivity. More importantly, due to the presence of reaction intermediates with extremely strong coordination ability during the hydrogenation process of quinoline compounds, the cycle life of the catalyst is greatly reduced, seriously affecting the service life of the catalyst. Therefore, how to provide a catalyst system with high catalytic activity, high selectivity and long cycle life has become a technical problem that needs to be solved urgently. Summary of the invention
[0006] In order to solve the problems in the prior art, the present invention provides a Ru-Ni bimetallic catalyst for selective hydrogenation of quinoline organic hydrogen storage carriers, and a preparation method and application thereof. The catalyst provided by the present invention has excellent catalytic hydrogenation performance in the selective hydrogenation of quinoline organic hydrogen storage carriers, and can omit the solvent from the reaction system. The reaction is not only simple and green, but also can guarantee the mass hydrogen storage density of the system when quinoline compounds are used as organic hydrogen carriers to the greatest extent. At the same time, the catalyst also has excellent cycle stability and can meet the commercial application requirements of N-heterocyclic organic hydrogen storage carriers.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a Ru-Ni bimetallic catalyst for selective hydrogenation of a quinoline organic hydrogen storage carrier, wherein the Ru-Ni bimetallic catalyst uses carbon nitride as a carrier, and metal nanoparticles Ru and Ni as active components are co-loaded on the carbon nitride carrier in a mass ratio of 5:(1.5-2.5);
[0009] The carbon nitride is prepared by a method comprising the following steps:
[0010] (1) mixing carbon tetrachloride, ethylenediamine and nano silicon dioxide with a particle size of 25-40 nm, and obtaining a carbon nitride polymer after reaction;
[0011] (2) The carbon nitride polymer obtained in step (1) is calcined at 750-850° C., desiliconized, filtered and dried to obtain a carbon nitride carrier.
[0012] The Ru-Ni bimetallic catalyst provided in the present invention is used for the selective hydrogenation of quinoline organic hydrogen storage carriers, specifically including the semi-hydrogenation of quinoline organic hydrogen storage carriers to generate the semi-hydrogenated product 1,2,3,4-tetrahydroquinoline (Py-THQ), and can also be used for the full hydrogenation of quinoline organic hydrogen storage carriers to generate decahydroquinoline (DHQ).
[0013] The Ru-Ni bimetallic catalyst provided by the present invention is used for the selective hydrogenation of quinoline organic hydrogen storage carriers, which can completely abandon the current practice of adding solvents to the reaction system, that is, in a reaction system without adding any solvents and additives, the Ru-Ni bimetallic catalyst provided by the present invention can achieve the selective hydrogenation of quinoline organic hydrogen storage carriers; and it can also ensure that at a lower temperature and a shorter time, a conversion rate of more than 95% is obtained, and the selectivity of semi-hydrogenated products and fully hydrogenated products reaches more than 95%; at the same time, the Ru-Ni bimetallic catalyst provided by the present invention also has excellent cycle stability, and even if it is recycled for more than 6 times, it can still ensure that the conversion rate of hydrogenation of quinoline compounds and the selectivity of the corresponding semi-hydrogenated and fully hydrogenated products are more than 95%.
[0014] Therefore, when the Ru-Ni bimetallic catalyst provided by the present invention is used for the selective hydrogenation of quinoline organic hydrogen storage carriers, it has the following advantages:
[0015] First, in the selective hydrogenation reaction system of quinoline organic hydrogen storage carriers, the addition of any form of solvent can be omitted. The omission of solvent can make the reaction simpler and greener, and more importantly, the use of a solvent-free system can maximize the mass hydrogen storage density of the system when quinoline compounds are used as organic hydrogen carriers, which is more conducive to the commercial application of organic hydrogen storage materials.
[0016] For example, with 1 g of quinoline as the reaction substrate, when 1 g of solvent is added to the system and decahydroquinoline is obtained through a full hydrogenation reaction, the molecular weight of decahydroquinoline is 139, and the molecular weight of the added hydrogen atom is 10. The mass hydrogen storage density calculation formula for this system is: 10 / 139 / (1 g+1 g)=0.036; however, in the system without adding solvent provided by the present invention, the mass hydrogen storage density is adjusted to: 10 / 139 / 1 g=0.0719, which is at least doubled compared to the system with solvent, thereby maximally ensuring the mass hydrogen storage density of the system when quinoline compounds are used as organic hydrogen carriers.
[0017] Secondly, although the present invention omits the addition of solvent, the conversion rate and product selectivity are not reduced accordingly. Moreover, surprisingly, while ensuring that the conversion rate and product selectivity are both above 95%, the temperature of the semi-hydrogenation reaction can be reduced to below 40°C, the temperature of the full hydrogenation reaction can be reduced to below 100°C, and the reaction time can be greatly shortened, thereby greatly saving reaction time and energy consumption.
[0018] Thirdly, the Ru-Ni bimetallic catalyst provided by the present invention not only ensures high catalytic activity and high selectivity when used for the first time, but also exhibits excellent stability when the catalyst is recycled. Even when recycled for the sixth time, the corresponding catalyst can still achieve a conversion rate of hydrogenation of quinoline compounds and a selectivity of the corresponding product of more than 95%, thereby greatly saving the catalyst cost and making the reaction system simpler and more efficient.
[0019] The Ru-Ni bimetallic catalyst provided by the present invention adopts carbon nitride prepared by a specific process as a carrier; through the combination of two active components, Ru and Ni, and the use of a specific carbon nitride carrier, a synergistic catalyst system is formed, which jointly achieves a high conversion rate during the selective hydrogenation of quinoline organic hydrogen storage carriers, high selectivity of corresponding products and high cycle stability, and makes it unnecessary to add a solvent in the corresponding reaction system, and the reaction temperature is lower and the reaction time is shorter.
[0020] In the present invention, when the Ru-Ni bimetallic catalyst is used for catalytic semi-hydrogenation or full hydrogenation of quinoline compounds, the temperature of the semi-hydrogenation reaction can be reduced to below 40° C. and the temperature of the full hydrogenation reaction can be reduced to below 100° C. while maintaining the same pressure as the current common reaction, and a conversion rate of more than 95% can be achieved in a shorter time, so that the selectivity of the semi-hydrogenation product 1,2,3,4-tetrahydroquinoline and the full hydrogenation product (DHQ) are both above 95%.
[0021] Taking quinoline as an example, by using the Ru-Ni bimetallic catalyst provided by the present invention, when the reaction pressure is 3Mpa, the reaction temperature is controlled to 40°C, and the reaction time is only 4 hours, the conversion rate can reach more than 95%, and the selectivity of the semi-hydrogenated product 1,2,3,4-tetrahydroquinoline is as high as more than 98%; while maintaining the pressure of 3Mpa, the reaction temperature is controlled to 100°C, and the reaction time is also only 4 hours, the conversion rate can be as high as more than 99%, and the selectivity of the fully hydrogenated product can also reach more than 95%.
[0022] In the Ru-Ni bimetallic catalyst provided by the present invention, the mass ratio of metal nanoparticles Ru and Ni is 5:(1.5-2.5), for example, it can be 5:1.5, 5:1.67, 5:1.8, 5:2, 5:2.2 or 5:2.5, and more preferably 5:(1.8-2.2).
[0023] The present invention controls the mass ratio of metal nanoparticles Ru and Ni to 5:(1.5-2.5), which can not only enable the catalyst to exert excellent catalytic activity and high selectivity, but also ensure that when the catalyst is recycled for more than 6 times, it can still ensure high conversion rate and high selectivity of hydrogenation of quinoline compounds, and further improve the service life of the catalyst. When Ru or Ni is used alone, it is impossible to ensure high activity and cycle stability of the catalyst at the same time, and the coordination of Ru and Ni elements will produce a synergistic effect; further, even when a combination of Ru and Ni is used, when the mass ratio of the two is not within the range of 5:(1.5-2.5), whether it is reducing Ru and increasing Ni, or increasing Ru and reducing Ni, it is impossible to well ensure high activity of the catalyst at the same time, and it is impossible to ensure high conversion rate and high selectivity of corresponding products during semi-hydrogenation and full hydrogenation catalysis at the same time, and the cycle stability of the catalyst will also deteriorate.
[0024] The present invention adopts a specific carbon nitride as a carrier. When the carbon nitride is replaced by a common carbon carrier, such as an activated carbon carrier, it will lead to a significant decrease in the conversion rate during semi-hydrogenation and a decrease in the selectivity of the product during full hydrogenation. Carbon as a carrier cannot simultaneously meet the requirements of having a conversion rate of more than 95% and a selectivity of more than 95% for the corresponding products during both semi-hydrogenation and full hydrogenation.
[0025] Furthermore, the carbon nitride (CN) carrier in the present invention is prepared by a specific method, especially by using nano-silica as a template and controlling its particle size, the specific surface area of the sample can be adjusted, the pore structure and the regular mesopore distribution can be controlled, so that it has a higher metal dispersion ability.
[0026] The present invention regulates the particle size of nano silicon dioxide to control it within the range of 25-40 nm (for example, 25 nm, 26 nm, 28 nm, 30 nm, 35 nm, 38 nm or 40 nm, etc.), so that it can provide a more suitable pore structure, so that the metal can be fully loaded and the utilization rate of the metal is improved; when the particle size of the nano silicon dioxide is less than 25 nm (for example, 15 nm), it will cause the pore size of the carrier to collapse inevitably, and it will become difficult for the metal to enter the carrier, thereby affecting the loading capacity; when the particle size of the nano silicon dioxide is greater than 40 nm (for example, 50 nm), due to the excessive pore size of the carrier, the loaded metal may be lost during several cycle experiments, which is not conducive to the reuse of the catalyst.
[0027] When preparing a carbon nitride carrier, the present invention adopts a raw material system consisting of carbon tetrachloride, ethylenediamine and nano-silicon dioxide, mixes the raw materials to react, obtains a carbon nitride polymer, and calcines the carbon nitride polymer at a temperature of 750-850°C (for example, 750°C, 780°C, 800°C, 810°C, 820°C or 850°C). By adopting a calcination temperature within this range, the carbon nitride can have an appropriate degree of graphitization. When the calcination temperature is too high (for example, 900°C), the degree of graphitization of the carbon nitride is too high, and the load capacity of the carrier becomes poor. When the calcination temperature is too low (for example, 700°C), the proportions of pyridinic nitrogen, pyrrolic nitrogen and graphitic nitrogen are unbalanced, so that the synergistic effect of the three nitrogens cannot be exerted, and the load capacity of the active component is reduced.
[0028] The carbon nitride carrier obtained by the preparation method provided by the present invention provides an ordered mesoporous structure and has the advantage of stable properties. Metal nanoparticles Ru and Ni are co-loaded on the carbon nitride carrier as active components. Its special pore structure can make the metal nanoparticles highly dispersed, and the reaction molecules can reside in the pores for a long time to ensure that the reaction can be fully carried out; and because the nitrogen doping process can introduce defect sites and nitrogen species, the physical and chemical properties of the catalyst are improved, and it can interact with the active species to enhance the catalytic performance, so that the selective hydrogenation of the quinoline organic hydrogen storage carrier can be better achieved.
[0029] Preferably, the calcination temperature in step (2) is 780-820°C.
[0030] The present invention further regulates the calcination temperature at 780-820° C., which can better exert the synergistic effect of three types of nitrogen, namely pyridinic nitrogen, pyrrolic nitrogen and graphitic nitrogen, thereby being more conducive to the selective hydrogenation of quinoline compounds.
[0031] Preferably, in the Ru-Ni bimetallic catalyst provided by the present invention, the particle sizes of the metal nanoparticles Ru and Ni are independently 3-4.5 nm, for example, 3 nm, 3.5 nm, 4 nm or 4.5 nm.
[0032] Preferably, based on the mass of the carbon nitride carrier as 100%, the total mass of the metal nanoparticles Ru and Ni accounts for 5-7%, for example, it can be 5%, 5.5%, 6%, 6.5% or 7%; the mass ratio of the metal nanoparticles Ru and Ni is 5:(1.5-2.5), for example, the mass proportion of the metal nanoparticles Ru can be 5%, the mass proportion of the metal nanoparticles Ni can be 2%, etc.
[0033] In a second aspect, the present invention provides a method for preparing a Ru-Ni bimetallic catalyst for selective hydrogenation of a quinoline organic hydrogen storage carrier as described in the first aspect, the preparation method comprising the following steps:
[0034] (1) mixing carbon tetrachloride, ethylenediamine and nano silicon dioxide with a particle size of 25-40 nm, and obtaining a carbon nitride polymer after reaction;
[0035] (2) calcining the carbon nitride polymer obtained in step (1) at 750-850° C., desiliconizing, filtering and drying to obtain a carbon nitride carrier;
[0036] (3) dissolving the carbon nitride carrier obtained in step (2) in water, and adding Ru 3+ and Ni 2+ The unreduced Ru-Ni bimetallic catalyst is obtained by ultrasonic impregnation and vacuum drying.
[0037] (4) reducing the unreduced Ru-Ni bimetallic catalyst obtained in step (3), raising the temperature, then cooling to room temperature and introducing a protective gas to obtain the Ru-Ni bimetallic catalyst.
[0038] The particle size of the nano-silicon dioxide in step (1) of the present invention is 25-40 nm, for example, it can be 25 nm, 26 nm, 28 nm, 30 nm, 35 nm, 38 nm or 40 nm.
[0039] The calcination temperature in step (2) of the present invention is 750-850°C, for example, it can be 750°C, 780°C, 800°C, 810°C, 820°C or 850°C, etc., preferably 780-820°C.
[0040] In the present invention, when the Ru-Ni bimetallic catalyst prepared by the corresponding preparation method is used for the semi-hydrogenation reaction of quinoline organic hydrogen storage carrier, it can improve the selectivity of the semi-hydrogenation product 1,2,3,4-tetrahydroquinoline (Py-THQ) to more than 98% at a temperature as low as 40°C, while also ensuring a conversion rate of more than 95%.
[0041] When the corresponding Ru-Ni bimetallic catalyst is used for the full hydrogenation reaction of quinoline organic hydrogen storage carriers, it can not only ensure that the selectivity of the full hydrogenation product is above 95% at a temperature as low as 100°C, but also the conversion rate of the full hydrogenation product can reach above 99%.
[0042] That is, the corresponding Ru-Ni bimetallic catalyst provided by the present invention can ensure a conversion rate of more than 95% and a selectivity of more than 95% for the corresponding products, regardless of whether it is used for the semi-hydrogenation reaction or the full hydrogenation reaction of the quinoline organic hydrogen storage carrier, which reflects that the catalyst has high catalytic activity in both semi-hydrogenation and full hydrogenation reactions.
[0043] Preferably, the mass ratio of carbon tetrachloride, ethylenediamine and nano-silicon dioxide in step (1) is (5-10):(2-4):1, wherein "(5-10)" can be 5, 7, 8, 10, etc.; "(2-4)" can be 2, 3, 4, etc.
[0044] Preferably, the calcination in step (2) is carried out in a tubular furnace; the temperature raising program of the tubular furnace is 2-4°C / min (e.g. 2°C / min, 2.5°C / min, 3°C / min, 4°C / min) and heated to 750-850°C for 3-5h (3h, 4h, 5h), and a protective gas (e.g. nitrogen) of 100-200mL / min (e.g. 100mL / min, 150mL / min, 200mL / min) is introduced into the entire calcination environment.
[0045] Preferably, the Ru added in step (3) 3+ The salt is RuCl3, and the added Ni 2+ The salt is Ni(OAc)2, and other types of ruthenium salts or nickel salts can also be added. 3+ Salt and Ni 2+ The amount of salt added is sufficient to make the mass ratio of Ru to Ni in the final prepared catalyst be 5:(1.5-2.5).
[0046] Preferably, the ultrasonic time in step (3) is 5-15 min (e.g. 5 min, 10 min, 15 min); the immersion time is 4-8 h (e.g. 4 h, 5 h, 6 h, 8 h), and the immersion temperature is 40-60°C (e.g. 40°C, 45°C, 50°C, 55°C, 60°C).
[0047] Preferably, the reduction temperature raising procedure in step (4) is 1-5°C / min (e.g. 1°C / min, 2.5°C / min, 3°C / min, 5°C / min) heated to 350-450°C (e.g. 350°C, 380°C, 400°C, 420°C, 450°C) and maintained for 1-3h (e.g. 1h, 2h, 3h), and 100-200mL / min (e.g. 100mL / min, 150mL / min, 200mL / min) of protective gas (e.g. nitrogen, etc.) is introduced into the entire reducing environment.
[0048] Preferably, the method for preparing the Ru-Ni bimetallic catalyst for selective hydrogenation of quinoline organic hydrogen storage carrier provided by the present invention may include the following steps:
[0049] (1) mixing carbon tetrachloride, ethylenediamine and nano-silicon dioxide in a mass ratio of (5-10):(2-4):1, reflux the obtained mixture at 80-100° C. for 5-10 h, then spin-drying the solvent to obtain a carbon nitride polymer, and placing the mixture in an oven at 100-120° C. overnight;
[0050] (2) placing the carbon nitride polymer obtained in step (1) into a tubular furnace and calcining at 750-850° C.; after cooling to room temperature, taking out the sample and crushing it; desiliconizing it with an acidic solution for 20-30 hours, filtering it, washing it with water until it is neutral, and drying it to obtain a carbon nitride carrier;
[0051] (3) dissolving the carbon nitride support obtained in step (2) in water, and adding Ru to the mixed system 3+ and Ni 2+ The salt solution is ultrasonicated and impregnated, the solvent is removed, and the catalyst is dried under vacuum to obtain an unreduced Ru-Ni bimetallic catalyst;
[0052] (4) The unreduced Ru-Ni bimetallic catalyst obtained in step (3) is placed in a tubular furnace for reduction, and nitrogen is introduced for protection after the temperature drops to room temperature, thereby finally obtaining a Ru-Ni bimetallic catalyst.
[0053] The preparation method related to the carbon nitride carrier provided in the second aspect of the present invention is also applicable to the preparation of the carbon nitride carrier in the first aspect of the present invention, and will not be described in detail here.
[0054] In a third aspect, the present invention provides an application of the Ru-Ni bimetallic catalyst for selective hydrogenation of quinoline organic hydrogen storage carriers according to the first aspect in catalyzing the selective hydrogenation and hydrogen storage of quinoline compounds.
[0055] Preferably, the Ru-Ni bimetallic catalyst can be used to catalyze both the semi-hydrogenation and the full hydrogenation of quinoline compounds.
[0056] In the present invention, whether the Ru-Ni bimetallic catalyst is used to catalyze the semi-hydrogenation or full hydrogenation reaction of quinoline compounds, it is carried out under solvent-free conditions.
[0057] The present invention can effectively avoid the addition of solvents in the prior art. Under solvent-free conditions, the present invention can still obtain a conversion rate of more than 95%, and the corresponding product selectivity reaches more than 95%. Based on this, it is also explained that the conversion rate and selectivity of the Ru-Ni bimetallic catalyst in the present invention are high; in addition, the reaction system can omit the solvent, the reaction is not only simple, green and environmentally friendly, but also can guarantee the mass hydrogen storage density of the system when the quinoline compound is used as the organic hydrogen carrier to the greatest extent, and the catalyst also has excellent cycle stability.
[0058] In the semi-hydrogenation or full hydrogenation reaction, the Ru-Ni bimetallic catalyst provided by the present invention only needs to have a molar ratio of Ru to quinoline compounds of 2-3% (e.g., 2%, 2.5% or 3%) to achieve a conversion rate of more than 95%, and the selectivity of the corresponding product is more than 95%, with high catalytic activity and high selectivity.
[0059] The application of the Ru-Ni bimetallic catalyst for catalyzing the semi-hydrogenation of quinoline compounds includes:
[0060] A quinoline compound is mixed with a Ru-Ni bimetallic catalyst, and reacted at 30-40° C. (eg, 30° C., 35° C., 38° C., 40° C.) to obtain a semi-hydrogenated product, 1,2,3,4-tetrahydroquinoline.
[0061] The conversion rate of the Ru-Ni bimetallic catalyst prepared in the present invention at 40°C can reach more than 95%, and the selectivity of the semi-hydrogenated product Py-THQ can reach more than 98%, while the conversion rate of commercial Ru / C at the same temperature and time is only 9.3%, which shows that the Ru-Ni bimetallic catalyst used in the present invention has a higher conversion rate.
[0062] The application of the Ru-Ni bimetallic catalyst for catalyzing the full hydrogenation of quinoline compounds includes:
[0063] A quinoline compound is mixed with a Ru-Ni bimetallic catalyst, and reacted at 80-100° C. (e.g., 80° C., 85° C., 90° C., 95° C., 100° C.) to obtain a fully hydrogenated product, decahydroquinoline.
[0064] The conversion rate of the Ru-Ni bimetallic catalyst prepared in the present invention at 100°C can reach more than 99%, and the selectivity of the full hydrogenation product DHQ can reach more than 95%, while the selectivity of commercial Ru / C at the same temperature and time is only about 35%, and the remaining 65% is the semi-hydrogenation product Py-THQ, which shows that the Ru-Ni bimetallic catalyst used in the present invention has higher selectivity.
[0065] In the present invention, when the Ru-Ni bimetallic catalyst is used for selective hydrogenation of quinoline organic hydrogen storage carrier, the pressure is only about 3 MPa, and the entire reaction can be carried out at a lower temperature and in a shorter time (4 h).
[0066] In the present invention, when the Ru-Ni bimetallic catalyst is used to catalyze the selective hydrogenation and hydrogen storage of quinoline compounds, the catalyst can be recycled for more than 6 times, and even when the Ru-Ni bimetallic catalyst is recycled for 6 times, the conversion rate of hydrogenation of quinoline compounds and the selectivity of corresponding products can still reach more than 95%, reflecting the excellent cycle stability of the catalyst.
[0067] The quinoline compound in the present invention may be, in addition to quinoline, the following quinoline compounds, which are not particularly limited in the present invention.
[0068]
[0069] For the above-mentioned quinoline compounds, the Ru-Ni bimetallic catalyst provided by the present invention is used, which can also achieve semi-hydrogenation catalysis with a conversion rate and a semi-hydrogenation product selectivity of more than 95% when the reaction temperature is as low as 40°C; at the same time, it can also achieve full hydrogenation catalysis with a conversion rate and a full hydrogenation product selectivity of more than 95% when the reaction temperature is as low as 100°C.
[0070] Compared with the prior art, the present invention has at least the following beneficial effects:
[0071] (1) The Ru-Ni bimetallic catalyst prepared by the present invention is a simple and green method. The metal nanoparticles Ru and Ni as active components can be highly dispersed on a carbon nitride carrier prepared by a specific process, and have a strong hydrogen binding ability. It can highly selectively obtain a semi-hydrogenated product (Py-THQ) at 40°C and a fully hydrogenated product (DHQ) at 100°C. In addition, the introduction of Ni significantly improves the catalytic activity and stability of the Ru catalyst.
[0072] (2) The Ru-Ni bimetallic catalyst provided by the present invention solves the problems of low catalytic activity, slow hydrogen storage rate, high reaction temperature, high price and short service life caused by catalyst instability in existing catalysts, and well meets the commercial application requirements of N-heterocyclic organic liquid hydrogen storage carriers (LOHC).
[0073] (3) The present invention can omit the solvent from the reaction system, which is not only simple and environmentally friendly, but also can guarantee the mass hydrogen storage density of the system to the greatest extent when quinoline compounds are used as organic hydrogen carriers. BRIEF DESCRIPTION OF THE DRAWINGS
[0074] Figure 1 This is a flow chart of the preparation of Ru-Ni / CN catalyst in Example 1.
[0075] Figure 2 This is the SEM image of the CN carrier prepared in Example 1.
[0076] Figure 3 XRD patterns of the CN support and Ru-Ni / CN catalyst prepared in Example 1.
[0077] Figure 4 This is the EDS image of the Ru-Ni / CN catalyst of Example 1.
[0078] Figure 5 This is the TEM image of the Ru-Ni / CN catalyst of Example 1.
[0079] Figure 6 This is the particle size distribution diagram of the Ru-Ni / CN catalyst of Example 1.
[0080] Figure 7 This is the lattice fringe diagram of the Ru-Ni / CN catalyst of Example 1.
[0081] Figure 8 The hydrogenation curves of the Ru-Ni / CN catalyst of Example 1 storing hydrogen to generate Py-THQ at different temperatures.
[0082] Fig. 9 The hydrogenation curves of the Ru-Ni / CN catalyst of Example 1 storing hydrogen to generate DHQ at different temperatures.
[0083] Fig.10 The graph shows the change in conversion rate and selectivity of fully hydrogenated DHQ after the Ru-Ni / CN catalyst of Example 1 is recycled for 6 times.
[0084] Fig.11 The graphs are the changes in conversion rate and selectivity of semi-hydrogenated Py-THQ after the Ru-Ni / CN catalyst of Example 1 was recycled for 6 times.
[0085] Fig.12 This is the Ru3P fine spectrum XPS graph of the Ru-Ni / CN catalyst in Example 1 before and after the reaction.
[0086] Fig.13 This is the NMR spectrum of the semi-hydrogenated product 1,2,3,4-tetrahydroquinoline prepared in Application Example 1-A.
[0087] Fig.14 This is the NMR spectrum of the fully hydrogenated product prepared in Application Example 1-B. DETAILED DESCRIPTION
[0088] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0089] The process equipment or devices not specifically specified in the following examples are all conventional equipment or devices in the art. Unless otherwise specified, the raw materials used in the examples of the present invention can be obtained commercially; unless otherwise specified, the technical means used in the examples of the present invention are all conventional means well known to those skilled in the art.
[0090] Example 1
[0091] This embodiment provides a Ru-Ni / CN catalyst, which uses carbon nitride (CN) as a carrier, and metal nanoparticles Ru and Ni are co-loaded on the CN carrier as active components, wherein the mass ratio of Ru to Ni is 5:2.
[0092] The Ru-Ni / CN catalyst is prepared by the following method: Figure 1 As shown, the following steps are included:
[0093] Step 1: Synthesis of CN carrier:
[0094] Carbon tetrachloride (24 g), ethylenediamine (10.8 g) and nano-silicon dioxide (30 nm, 3.2 g) were added to a 100 mL round-bottom flask, and the mixture was refluxed at 90° C. for 6 h, and then the solvent was spin-dried to obtain a CN polymer, which was placed in an oven at 120° C. overnight; then the CN polymer was placed in a tubular furnace, heated to 800° C. at a rate of 3° C. / min and maintained for 5 h, and 150 mL / min of nitrogen protection was introduced into the entire calcination environment; after cooling to room temperature, the sample was taken out and crushed; desiliconized with 40 mL HF solution (mass fraction of 10%) for 24 h, filtered, washed with pure water until neutral, and dried to obtain a CN carrier.
[0095] Step 2: Loading metal nanoparticles Ru and Ni on the CN carrier:
[0096] Anhydrous ruthenium trichloride (RuCl3) and Ni(OAc)2 were dissolved in an appropriate amount of H2O so that the mass fraction of the added metal Ru accounted for 5% of the CN carrier and the mass fraction of the added metal Ni accounted for 2% of the CN carrier, and were slowly added to a round-bottom flask containing the CN carrier, ultrasonically treated for 10 minutes, and statically mixed at 50°C for 6 hours. The solvent was dried using a rotary evaporator and placed in an oven at 120°C to obtain an unreduced CN sample; then, the CN sample to be reduced was placed in a tubular furnace, heated to 400°C at a rate of 3°C / min in H2 (150mL / min) and maintained for 2 hours, and when it cooled to room temperature, 150mL / min of nitrogen was introduced for protection, and taken out after 1 hour to obtain a Ru-Ni / CN catalyst.
[0097] Figure 2 This is the SEM image of the CN carrier prepared in this example. Figure 2It can be seen that the pores and pore-like structures of the CN carrier are similar to the morphology of the cross-linked polymerization of the nano-silica template used, which shows that the use of nano-silica as a template can obtain porous carbon nitride with stronger metal loading capacity, and the corresponding carrier structure can enhance the utilization rate of metal particles.
[0098] Figure 3 The XRD patterns of the CN carrier and Ru-Ni / CN catalyst prepared in this example are shown in FIG. Figure 3 It can be seen that only two broad peaks located near 24.0° and 44.1° were observed for the CN support and Ru-Ni / CN catalyst, which belong to the (002) and (001) planes of graphite, respectively, and the crystallinity of the CN support is low. When the crystallinity of the catalyst support is low, its lattice structure tends to be loose, and there are many disordered regions and defects. These regions and defects provide abundant active sites for the catalyst, making it easier for reactant molecules to approach and adsorb on the catalyst surface, thereby accelerating the catalytic reaction. In the Ru-Ni / CN sample, no peaks corresponding to metallic Ru (JCPDS No. 06-0663), metallic Ni (JCPDS No. 04-085) and bimetallic Ru-Ni (JCPDS No. 65-6490) were detected, indicating that there are no large-sized metal nanoparticles on the surface of the CN support, indicating that Ru and Ni atoms are highly dispersed on the surface of the CN support.
[0099] Figure 4 is the element EDS distribution diagram of the Ru-Ni / CN catalyst of this embodiment, Figure 4 It can be seen that the Ru and Ni nanoparticles are evenly distributed on the surface of the CN support.
[0100] Figure 5 is the TEM image of the Ru-Ni / CN catalyst of this embodiment, Figure 5 It can be seen that the Ru and Ni nanoparticles are highly dispersed on the CN support.
[0101] Figure 6 is the particle size distribution diagram of the Ru-Ni / CN catalyst of this embodiment, Figure 6 It can be seen that the average particle size of the Ru-Ni bimetallic nanoparticles is 3.9 ± 0.5 nm.
[0102] Figure 7 is a lattice fringe photograph of the Ru-Ni / CN catalyst of this embodiment, from Figure 7 Clear lattice fringes can be seen in the figure. The lattice spacing of the nanoparticles of the Ru-Ni / CN catalyst is only 0.224 nm, which well proves that the interaction between atoms or ions in the lattice of the catalyst becomes stronger, which can better play the synergistic effect between the metal and the carrier.
[0103] Example 2
[0104] This embodiment provides a Ru-Ni / CN catalyst, wherein the catalyst uses CN as a carrier, and metal nanoparticles Ru and Ni are co-loaded on the CN carrier as active components, wherein the mass ratio of Ru to Ni is 5:1.8.
[0105] The Ru-Ni / CN catalyst is prepared by the following method, which specifically comprises the following steps:
[0106] Step 1: Synthesis of CN carrier:
[0107] Carbon tetrachloride (20 g), ethylenediamine (8 g) and nano-silicon dioxide (25 nm, 2 g) were added to a 100 mL round-bottom flask, and the mixture was refluxed at 80° C. for 5 h, and then the solvent was spin-dried to obtain a CN polymer, which was placed in an oven at 120° C. overnight, and then the CN polymer was placed in a tubular furnace, heated to 795° C. at a rate of 3° C. / min and maintained for 3 h, and 100 mL / min of nitrogen protection was introduced into the entire calcination environment; after cooling to room temperature, the sample was taken out and crushed; desiliconized with 40 mL HF solution (mass fraction of 5%) for 20 h, filtered, washed with pure water until neutral, and dried to obtain a CN carrier.
[0108] Step 2: Loading metal nanoparticles Ru and Ni on the CN carrier:
[0109] Anhydrous ruthenium trichloride (RuCl3) and Ni(OAc)2 were dissolved in an appropriate amount of H2O so that the mass fraction of the added metal Ru accounted for 5% of the CN carrier and the mass fraction of the added metal Ni accounted for 1.8% of the CN carrier, and were slowly added to a round-bottom flask containing the CN carrier, ultrasonically treated for 10 minutes, and statically mixed at 30°C for 3 hours. The solvent was dried using a rotary evaporator and placed in an oven at 100°C to obtain an unreduced CN sample; then, the CN sample to be reduced was placed in a tubular furnace, heated to 380°C at a rate of 5°C / min in H2 (150mL / min) and maintained for 2 hours, and when it cooled to room temperature, 150mL / min of nitrogen was introduced for protection, and taken out after 1 hour to obtain a Ru-Ni / CN catalyst.
[0110] Example 3
[0111] This embodiment provides a Ru-Ni / CN catalyst, wherein the catalyst uses CN as a carrier, and metal nanoparticles Ru and Ni are co-loaded on the CN carrier as active components, wherein the mass ratio of Ru to Ni is 5:2.2.
[0112] The Ru-Ni / CN catalyst is prepared by the following method, which specifically comprises the following steps:
[0113] Step 1: Synthesis of CN carrier:
[0114] Carbon tetrachloride (28 g), ethylenediamine (12 g) and nano-silicon dioxide (30 nm, 5 g) were added to a 100 mL round-bottom flask, and the mixture was refluxed at 100 ° C for 8 h, and then the solvent was spin-dried to obtain a CN polymer, which was placed in an oven at 120 ° C overnight, and then the CN polymer was placed in a tubular furnace, heated to 805 ° C at a rate of 3 ° C / min for 5 h, and 150 mL / min of nitrogen protection was introduced in the entire calcination environment; after cooling to room temperature, the sample was taken out and crushed; desiliconized with 40 mL HF solution (mass fraction of 15%) for 30 h, filtered, washed with pure water until neutral, and dried to obtain a CN carrier.
[0115] Step 2: Loading metal nanoparticles Ru and Ni on the CN carrier:
[0116] Anhydrous ruthenium trichloride (RuCl3) and Ni(OAc)2 were dissolved in an appropriate amount of H2O so that the mass fraction of the added metal Ru accounted for 5% of the CN carrier and the mass fraction of the added metal Ni accounted for 2.2% of the CN carrier, and were slowly added to a round-bottom flask containing the CN carrier, ultrasonically treated for 10 minutes, and statically mixed at 60°C for 8 hours. The solvent was dried using a rotary evaporator and placed in an oven at 140°C to obtain an unreduced CN sample; then, the CN sample to be reduced was placed in a tubular furnace, heated to 400°C at a rate of 5°C / min in H2 (150mL / min) and maintained for 3 hours, and when it cooled to room temperature, 150mL / min of nitrogen was introduced for protection, and taken out after 1 hour to obtain a Ru-Ni / CN catalyst.
[0117] Examples 4 to 9
[0118] Compared with Example 1, only the calcination temperature when preparing the CN carrier in step 1 (Examples 4 to 5), the particle size of the added nano-silicon dioxide (Examples 6 to 7) and the mass ratio of Ru and Ni added when preparing the catalyst in step 2 (here refers to the mass ratio of metal nanoparticles Ru and Ni in the final catalyst product) (Examples 8 to 9) were changed, as shown in Table 1, wherein "——" means the same as Example 1, and the corresponding CN carrier was obtained, and the other conditions were the same as Example 1.
[0119] Table 1
[0120] Calcination temperature Nanosilica particle size Mass ratio of Ru and Ni in the catalyst Example 1 800℃ 30nm 5:2 Example 4 780℃ —— —— Example 5 820℃ —— —— Example 6 —— 25nm —— Example 7 —— 40nm —— Example 8 —— —— 5:1.7 Example 9 —— —— 5:2.5
[0121] Comparative Example 1
[0122] This comparative example provides a Ru / C catalyst, which differs from Example 1 in that the CN carrier is directly replaced by activated carbon, and the active component is replaced by a single Ru element, the mass ratio of Ru to C carrier is 7%, and the rest is the same as Example 1.
[0123] Comparative Example 2
[0124] This comparative example provides a Ru / CN catalyst, which is different from Example 1 only in that the active component is replaced by a single Ru element, the mass ratio of Ru to CN carrier is 7%, and the rest is the same as Example 1.
[0125] Comparative Example 3
[0126] This comparative example provides a Ni / CN catalyst, which is different from Example 1 only in that the active component is replaced by a single Ni element, the mass ratio of Ni to CN carrier is 7%, and the rest is the same as Example 1.
[0127] Comparative Example 4
[0128] This comparative example provides a Ru-Ni / C catalyst, which is different from Example 1 only in that the CN carrier is directly replaced by activated carbon, and the rest is the same as Example 1.
[0129] Comparative Example 5
[0130] This comparative example provides a Ru-Ni / CN catalyst, which is different from Example 1 only in that the preparation method of the CN carrier is adjusted to the following steps, and the rest is the same as Example 1.
[0131] 6.0 g of urea was calcined at 500° C. in a calcining furnace in a nitrogen atmosphere at a heating rate of 5° C. / min for 2 h; the obtained material was ground into powder and washed with water several times in sequence, and then the obtained product was dried at 60° C. for 12 h to obtain a CN carrier.
[0132] Comparative Example 6
[0133] This comparative example provides a Ru-Ni / CN catalyst, which is different from Example 1 only in that the nano-silica added in the preparation of the CN carrier is adjusted to the mesoporous molecular sieve SBA-15 as a template, and the rest is the same as Example 1.
[0134] Comparative Example 7
[0135] This comparative example provides a Ru-Ni / CN catalyst, which is different from Example 1 only in that the calcination temperature during the preparation of the CN carrier is adjusted to 700° C., and the rest is the same as Example 1.
[0136] Comparative Example 8
[0137] This comparative example provides a Ru-Ni / CN catalyst, which is different from Example 1 only in that the calcination temperature during the preparation of the CN carrier is adjusted to 900° C., and the rest is the same as Example 1.
[0138] Comparative Example 9
[0139] This comparative example provides a Ru-Ni / CN catalyst, which is different from Example 1 only in that the particle size of the nano-silicon dioxide added in the preparation of the CN carrier is adjusted to 15 nm, and the rest is the same as Example 1.
[0140] Comparative Example 10
[0141] This comparative example provides a Ru-Ni / CN catalyst, which is different from Example 1 only in that the particle size of the nano-silicon dioxide added in the preparation of the CN carrier is adjusted to 50 nm, and the rest is the same as Example 1.
[0142] Comparative Example 11
[0143] This comparative example provides a Ru-Ni / CN catalyst, which differs from Example 1 only in that the mass ratio of the active components Ru and Ni is adjusted to 5:3.3, the mass fraction of metal Ru in the catalyst accounts for 5% of the CN carrier, and the mass fraction of the added metal Ni accounts for 3.3% of the CN carrier. The rest is the same as Example 1.
[0144] Comparative Example 12
[0145] This comparative example provides a Ru-Ni / CN catalyst, which differs from Example 1 only in that the mass ratio of the active components Ru and Ni is adjusted to 5:3, the mass fraction of metal Ru in the catalyst accounts for 5% of the CN carrier, and the mass fraction of the added metal Ni accounts for 3% of the CN carrier, and the rest is the same as Example 1.
[0146] Comparative Example 13
[0147] This comparative example provides a Ru-Ni / CN catalyst, which differs from Example 1 only in that the mass ratio of the active components Ru and Ni is adjusted to 5:1, the mass fraction of metal Ru in the catalyst accounts for 5% of the CN carrier, and the mass fraction of the added metal Ni accounts for 1% of the CN carrier. The rest is the same as Example 1.
[0148] The catalysts prepared in Examples 1 to 9 and Comparative Examples 1 to 13 were used for the selective hydrogenation of quinoline.
[0149] Application Example 1-A
[0150] This application example provides a method for catalyzing semi-hydrogenation of quinoline, which comprises the following steps:
[0151] Quinoline was mixed with the Ru-Ni / CN catalyst prepared in Example 1, wherein the amount of the Ru-Ni / CN catalyst was mixed according to a molar ratio of Ru to quinoline in the catalyst of 2%, and the mixture was reacted at 40° C. and a pressure of 3 MPa for 4 h to obtain a semi-hydrogenated product 1,2,3,4-tetrahydroquinoline with a conversion rate of 99% and a selectivity of 99% for the semi-hydrogenated product 1,2,3,4-tetrahydroquinoline.
[0152] The reaction process is as follows:
[0153]
[0154] The semi-hydrogenated product 1,2,3,4-tetrahydroquinoline prepared in this application example is characterized as follows Fig.13 shown.
[0155] Comparative Application Example 1-A
[0156] This comparative application example provides a method for catalyzing the semi-hydrogenation of quinoline, which comprises the following steps:
[0157] Quinoline was mixed with the Ru / C catalyst prepared in Comparative Example 1, wherein the amount of the Ru / C catalyst was such that the molar ratio of Ru to quinoline in the catalyst was 2%. The mixture was reacted at 40° C. and a pressure of 3 MPa for 4 h to obtain a semi-hydrogenated product, 1,2,3,4-tetrahydroquinoline, with a conversion rate of 9.3%.
[0158] Based on Application Example 1-A, the reaction temperature was adjusted from 40°C to 30°C and 50°C to form Figure 8 The hydrogenation curves of the Ru-Ni / CN catalyst of Example 1 at different temperatures (30°C, 40°C, 50°C) for generating Py-THQ are shown. Figure 8 It can be seen that when the reaction temperature is 40°C, the conversion rate in 0.5h can reach 11%, from which it can be concluded that the present invention can not only greatly improve the conversion rate by adopting the corresponding Ru-Ni / CN catalyst, but also greatly shorten the reaction time and improve the reaction efficiency. This also fully demonstrates that the Ru-Ni / CN catalyst provided by the present invention has higher catalytic activity in quinoline semi-hydrogenation.
[0159] Application Examples 2-A to 9-A and Comparative Examples Application Examples 2-A to 13-A
[0160] Compared with Application Example 1-A, only the catalyst in Example 1 is replaced by the catalysts prepared in Examples 2 to 9 and Comparative Examples 2 to 13. Since Comparative Example 3 contains only Ni element as the active component, when it is used for semi-hydrogenation, the molar ratio of Ni to quinoline in the catalyst is 2%. The rest is the same as Application Example 1-A.
[0161] The semi-hydrogenation catalytic effects of Application Examples 1-A to 9-A and Comparative Application Examples 1-A to 13-A are shown in Table 2.
[0162] Table 2
[0163]
[0164]
[0165] It can be seen from Table 2 that:
[0166] (1) Application Examples 1-A to 9-A can all achieve a conversion rate greater than 95%, and the selectivity of Py-THQ is greater than 98%. Application Examples 1-A to 3-A can even achieve a conversion rate greater than 99%, and the selectivity of Py-THQ reaches greater than 99%.
[0167] (2) By comparing Application Examples 1-A, 4-A and 5-A with Comparative Application Examples 7-A and 8-A, it can be seen that when the calcination temperature during the preparation of the CN carrier is too low (700°C), the conversion rate will drop to about 80%. When the calcination temperature is too high (900°C), the conversion rate will also drop, and the selectivity of Py-THQ will also decrease. When the calcination temperature is controlled at 780-820°C, the conversion rate can be greater than 95%, and the selectivity of Py-THQ is above 98%.
[0168] (3) By comparing Application Examples 1-A, 6-A and 7-A with Comparative Application Examples 9-A and 10-A, it can be seen that when the particle size of nano-silica is too small (15nm) when preparing the CN carrier, it will cause the conversion rate to drop to about 85%, while when the particle size of nano-silica is too large (50nm), the conversion rate is 94%, and when the particle size of nano-silica is controlled at 25-40nm, it can make the conversion rate greater than 95%, and the selectivity of Py-THQ is above 98%.
[0169] (4) By comparing Application Examples 1-A, 8-A and 9-A with Comparative Application Examples 11-A to 13-A, it can be seen that when the mass ratio of Ru and Ni changes, although the element ratio of Ru in the reaction system remains unchanged, however, based on the catalyst provided in Example 1, when the Ni element content decreases or increases, it will affect the conversion rate and the conversion rate of Py-THQ. For example, when a smaller amount of Ni element is added than in Example 1 in Comparative Example 13, the conversion rate drops to 89.2%. When the Ni element ratio is increased to more than 2.5, the catalysts provided in Comparative Examples 11 to 12 cause the conversion rate to drop even more. Only when the mass ratio of Ru and Ni is regulated in an appropriate range (5:(1.5-2.5)), the conversion rate reaches a level of more than 95%.
[0170] (5) Comparing Application Example 1-A with Comparative Application Examples 1-A to 6-A, when Ru element alone or Ni element alone is used, and when the CN carrier is replaced, a conversion rate of more than 95% cannot be achieved. This also proves that the Ru and Ni elements are used in a specific combination in the present invention and loaded on a CN carrier obtained by a specific preparation method, which produces a synergistic effect and cooperates with each other to achieve a conversion rate of more than 95%, and the selectivity of Py-THQ reaches more than 98%.
[0171] Application Example 1-B
[0172] This application example provides a method for catalytic full hydrogenation of quinoline, which comprises the following steps:
[0173] Quinoline was mixed with the Ru-Ni / CN catalyst prepared in Example 1, wherein the amount of the Ru-Ni / CN catalyst was such that the molar ratio of Ru to quinoline in the catalyst was 2%, and the mixture was reacted at 100° C. and a pressure of 3 MPa for 4 h to obtain a fully hydrogenated product, decahydroquinoline, with a selectivity of 99%.
[0174] The reaction process is as follows:
[0175]
[0176] The fully hydrogenated product decahydroquinoline prepared in this application example is characterized as follows Fig.14 shown.
[0177] Comparative Application Example 1-B
[0178] This comparative application example provides a method for catalytic full hydrogenation of quinoline, which comprises the following steps:
[0179] Quinoline was mixed with the Ru / C catalyst prepared in Comparative Example 1, wherein the amount of the Ru / C catalyst was such that the molar ratio of Ru to quinoline in the catalyst was 2%. The mixture was reacted at 100° C. and a pressure of 3 MPa for 4 h to obtain a fully hydrogenated product, decahydroquinoline, with a selectivity of 35.1%.
[0180] Based on Application Example 1-B, the reaction temperatures were adjusted to 80°C and 120°C, respectively, to form Fig. 9 The hydrogenation curves of the Ru-Ni / CN catalyst of Example 1 at different temperatures (80°C, 100°C, 120°C) for storing hydrogen to generate DHQ are shown. Fig. 9 It can be seen that when the reaction temperature is 100°C, the conversion rate of 1.5h has exceeded 40%, from which it can be concluded that the present invention can not only greatly improve the selectivity by adopting the corresponding Ru-Ni / CN catalyst, but also shorten the reaction time and improve the reaction efficiency. This also fully illustrates that the Ru-Ni / CN catalyst provided by the present invention has higher catalytic activity and higher selectivity in quinoline full hydrogenation.
[0181] Application Examples 2-B to 9-B and Comparative Examples Application Examples 2-B to 13-B
[0182] Compared with Application Example 1-B, only the catalyst in Example 1 is replaced by the catalysts prepared in Examples 2 to 9 and Comparative Examples 2 to 13. Since Comparative Example 3 contains only Ni element as the active component, when it is used for full hydrogenation, the molar ratio of Ni and quinoline in the catalyst is 2%, and the rest is the same as Application Example 1-B.
[0183] The full hydrogenation catalytic effects of Application Examples 1-B to 9-B and Comparative Application Examples 1-B to 13-B are shown in Table 3.
[0184] Table 3
[0185]
[0186]
[0187] It can be seen from Table 5 that:
[0188] (1) Application Examples 1-B to 9-B can achieve a conversion rate of more than 99%, and the selectivity of DHQ is more than 95%.
[0189] (2) By comparing application examples 1-B, 4-B and 5-B with comparative application examples 7-B and 8-B, and by comparing application examples 1-B, 6-B and 7-B with comparative application examples 9-B and 10-B, it can be seen that when preparing the CN carrier, when the calcination temperature is 780-820°C and the particle size of the nano-silica is controlled at 25-40nm, the selectivity of DHQ can be maintained above 95%. However, when the calcination temperature is too high or too low, and the particle size of the nano-silica is too large or too small, the selectivity of DHQ will decrease.
[0190] (3) When Application Example 1-B is compared with Comparative Application Examples 2-B to 3-B, when the same CN carrier is used and the active component is adjusted to a single Ru element or a single Ni element, it is impossible to achieve the 99% DHQ selectivity that can be achieved by combining Ru and Ni elements in Application Example 1-B. Even when only Ni is used as the active component, it is impossible to catalyze the quinoline compound to achieve a full hydrogenation reaction. This fully demonstrates that the combination of Ru and Ni elements produces a synergistic effect, which jointly promotes the full hydrogenation catalytic reaction of quinoline compounds.
[0191] (4) Application Example 1-B is compared with Comparative Application Examples 4-B to 6-B. When the same active component is used and the corresponding CN carrier is changed to an activated carbon carrier or a CN carrier obtained by other preparation methods, it is also impossible to achieve the DHQ selectivity of 99% achieved in Application Example 1-B. In particular, when the CN carrier is replaced with a carbon carrier, its DHQ selectivity is greatly reduced. This also shows that by adopting the CN carrier obtained by the corresponding preparation method of the present invention, the full hydrogenation catalytic reaction of quinoline compounds can be better achieved, making the DHQ selectivity higher.
[0192] (5) Application Example 1-B is compared with Comparative Application Examples 11-B to 13-B. Although they all use a combination of Ru and Ni elements, when the Ru content remains unchanged, changing the Ni content will lead to a decrease in DHQ selectivity compared to increasing or decreasing the Ni content in Example 1. On the contrary, when the mass ratio of Ru and Ni elements is in the range of 5:(1.5-2.5), the DHQ selectivity can reach more than 95% while ensuring a conversion rate of 99%.
[0193] In summary, it can be seen from Application Examples 1-A to 9-A and Application Examples 1-B to 9-B that in the present invention, by compounding the Ni element and the Ru element and combining them with a CN carrier prepared by a specific method, a synergistic effect is produced between them. The catalyst is used in the semi-hydrogenation and full hydrogenation catalytic reactions of quinoline compounds, and a conversion rate of more than 95% can be achieved, and the selectivity of the semi-hydrogenated product 1,2,3,4-tetrahydroquinoline and the full hydrogenation product decahydroquinoline both reach more than 95%.
[0194] Catalyst repeatability test (taking full hydrogenation as an example)
[0195] Test Example 1
[0196] On the basis of Example 1, the Ni element in the catalyst is replaced by Co, Fe and Pt respectively to form Ru-Co / CN catalyst, Ru-Fe / CN catalyst and Ru-Pt / CN catalyst. The other conditions are exactly the same as those in Example 1. These three catalysts replace the catalyst in Application Example 1-B to form Comparative Application Example 1-B', Comparative Application Example 2-B' and Comparative Application Example 3-B'.
[0197] The catalyst used in Application Example 1-B and Comparative Application Examples 1-B to 2-B and Comparative Application Examples 1-B' to 3-B' after one reaction was reused once; during the repeated use, the reaction temperature, pressure and time remained unchanged, and the results of the full hydrogenation are shown in Table 4.
[0198] Table 4
[0199]
[0200]
[0201] It can be seen from Table 4 that:
[0202] After the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 are recycled once, the selectivity of the fully hydrogenated products will be greatly different. The selectivity of the Ru / C catalyst prepared in Comparative Example 1 will drop to 11.3% after being recycled once, and the selectivity of the Ru / CN catalyst prepared in Comparative Example 2 will drop to 71.9% after being recycled once; the selectivity will also drop after replacing the Ni element with Co, Fe and Pt. The Ru-Ni / CN catalyst prepared in Example 1 of the present invention, even if it is recycled once, its selectivity remains at 99%, which shows that the Ru-Ni / CN catalyst provided in the present invention has a good cycle life.
[0203] It can also be seen from the data in Table 4 that when only Ru is used as an active component, carbon nitride is used as a carrier (catalyst in comparative example 2), it has better selectivity and stronger cycle stability than carbon as a carrier (catalyst in comparative example 1), but after one cycle, the selectivity still decreases. In the present invention, Ru and Ni elements are used for specific coordination, and carbon nitride is also used as a carrier. Compared with only using Ru as an active component, it shows greater advantages in cycle stability, and still maintains 99% selectivity after one cycle, which fully reflects that the present invention uses Ru and Ni elements and carbon nitride carriers, which have a synergistic relationship with each other, and jointly improve the selectivity and cycle repeatability of the catalyst.
[0204] Fig.10 The figure shows the change in conversion rate and selectivity of fully hydrogenated DHQ after 6 cycles of using the Ru-Ni / CN catalyst prepared in Example 1 of the present invention; Fig.11 The graph shows the change in conversion rate and selectivity of semi-hydrogenated Py-THQ after 6 cycles of using the Ru-Ni / CN catalyst prepared in Example 1 of the present invention.
[0205] pass Fig.10 and Fig.11 It can be seen that the high activity and high selectivity of the Ru-Ni / CN catalyst provided by the present invention do not change with the increase in the number of cycles, and the conversion rate of quinoline hydrogenation and the selectivity of the corresponding product are maintained at more than 95% in 6 cycles.
[0206] Fig.12 The Ru3P fine spectrum XPS graph of the Ru-Ni / CN catalyst prepared in Example 1 of the present invention before and after the reaction is shown. Fig.12 It can also be seen that the area ratio of Ru0 and Run+ of the Ru-Ni / CN catalyst provided by the present invention before and after the reaction is basically maintained at 3:2, which further confirms that the Ru-Ni / CN catalyst provided by the present invention can still maintain high activity even when recycled.
[0207] Therefore, the Ru-Ni / CN catalyst provided by the present invention not only has better selectivity than the catalysts of Comparative Examples 1 and 2 when cycled once, but even after cycling 6 times, it still has a conversion rate of more than 95%, and the selectivity of the corresponding product can also be maintained at more than 95%, which illustrates the excellent cycle stability of the corresponding catalyst of the present invention.
[0208] In summary, the Ru-Ni / CN catalyst provided by the present invention can achieve a conversion rate of more than 95% in a solvent-free system at a lower temperature and in a shorter time, and the selectivity of the semi-hydrogenated product and the fully hydrogenated product both reach more than 95%; at the same time, it also has excellent cycle stability, and even if it is recycled for more than 6 times, it can still ensure that the conversion rate and selectivity of the hydrogenation of quinoline compounds are more than 95%, effectively solving the problems of low catalytic activity, slow hydrogen storage rate, high reaction temperature, high price, and short service life caused by catalyst instability in existing catalysts, and well meets the commercial application requirements of N-heterocyclic organic liquid hydrogen storage carriers (LOHC).
Claims
1. A Ru-Ni bimetallic catalyst for selective hydrogenation of quinoline organic hydrogen storage carriers, characterized in that: The Ru-Ni bimetallic catalyst uses carbon nitride as a carrier, and metal nanoparticles Ru and Ni are co-loaded on the carbon nitride carrier in a mass ratio of 5:(1.5-2.5) as active components; The carbon nitride is prepared by a method comprising the following steps: (1) mixing carbon tetrachloride, ethylenediamine and nano silicon dioxide with a particle size of 25-40 nm, and obtaining a carbon nitride polymer after reaction; (2) The carbon nitride polymer obtained in step (1) is calcined at 750-850° C., desiliconized, filtered and dried to obtain a carbon nitride carrier.
2. The Ru-Ni bimetallic catalyst according to claim 1, characterized in that The particle sizes of the metal nanoparticles Ru and Ni are independently 3-4.5 nm; Preferably, in the preparation of the carbon nitride, the calcination temperature in step (2) is 780-820°C.
3. A method for preparing a Ru-Ni bimetallic catalyst for selective hydrogenation of a quinoline organic hydrogen storage carrier according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) mixing carbon tetrachloride, ethylenediamine and nano silicon dioxide with a particle size of 25-40 nm, and obtaining a carbon nitride polymer after reaction; (2) calcining the carbon nitride polymer obtained in step (1) at 750-850° C., desiliconizing, filtering and drying to obtain a carbon nitride carrier; (3) dissolving the carbon nitride carrier obtained in step (2) in water, and adding Ru 3+ and Ni 2+ The unreduced Ru-Ni bimetallic catalyst is obtained after ultrasonic impregnation and vacuum drying. (4) reducing the unreduced Ru-Ni bimetallic catalyst obtained in step (3), raising the temperature, then cooling to room temperature and introducing a protective gas to obtain the Ru-Ni bimetallic catalyst.
4. The preparation method according to claim 3, characterized in that: The calcination temperature in step (2) is 780-820°C.
5. The preparation method according to claim 3 or 4, characterized in that: The mass ratio of carbon tetrachloride, ethylenediamine and nano-silicon dioxide in step (1) is (5-10):(2-4):1; Preferably, the calcination in step (2) is carried out in a tubular furnace; Preferably, the temperature raising program in the tube furnace is: heating to 750-850° C. at 2-4° C. / min and maintaining for 3-5 hours, and introducing 100-200 mL / min of protective gas into the whole calcination environment.
6. The preparation method according to any one of claims 3 to 5, characterized in that: Ru added in step (3) 3+ The salt is RuCl3, and the added Ni 2+ The salt is Ni(OAc)2; Preferably, the Ru 3+ Salt and Ni 2+ The amount of salt added is such that the mass ratio of the metal nanoparticles Ru and Ni in the Ru-Ni bimetallic catalyst is 5:(1.5-2.5); Preferably, the ultrasonic time in step (3) is 5-15 minutes; the immersion time is 4-8 hours, and the immersion temperature is 40-60°C; Preferably, the reduction temperature raising procedure in step (4) is: heating to 350-450°C at 1-5°C / min and maintaining for 1-5h, and introducing 100-200mL / min of protective gas into the entire reducing environment.
7. Use of the Ru-Ni bimetallic catalyst for selective hydrogenation of quinoline organic hydrogen storage carrier according to claim 1 or 2 in catalyzing the selective hydrogenation and hydrogen storage of quinoline compounds.
8. The use according to claim 7, characterized in that: The Ru-Ni bimetallic catalyst is used to catalyze the semi-hydrogenation and / or full hydrogenation of quinoline compounds; Preferably, the Ru-Ni bimetallic catalyst catalyzes the selective hydrogenation of quinoline compounds in the absence of solvent; Preferably, in the semi-hydrogenation or full hydrogenation reaction, the molar ratio of Ru to quinoline compound in the Ru-Ni bimetallic catalyst is 2-3%.
9. The use according to claim 8, characterized in that: The application of the Ru-Ni bimetallic catalyst for catalyzing the semi-hydrogenation of quinoline compounds includes: The quinoline compound is mixed with a Ru-Ni bimetallic catalyst and reacted at 30-40° C. to obtain a semi-hydrogenated product 1,2,3,4-tetrahydroquinoline; Preferably, the application of the Ru-Ni bimetallic catalyst for catalyzing the full hydrogenation of quinoline compounds includes: The quinoline compound is mixed with a Ru-Ni bimetallic catalyst, and reacted at 80-100 DEG C to obtain a fully hydrogenated product, decahydroquinoline.
10. The use according to any one of claims 7 to 9, characterized in that: When the Ru-Ni bimetallic catalyst is used to catalyze the selective hydrogenation and hydrogen storage of quinoline compounds, the catalyst can be recycled for ≥6 times; Preferably, when the Ru-Ni bimetallic catalyst is recycled for 6 times, the conversion rate of hydrogenation of quinoline compounds is above 95%, and the selectivity of the corresponding semi-hydrogenated or fully hydrogenated products is above 95%.
Citation Information
Patent Citations
Palladium-supported mesoporous carbon nitride catalyst for bromate reduction and preparation
CN102895986A
Preparation method and application of non-noble metal and noble metal bimetallic catalyst for hydrogenation and dehydrogenation of organic hydrogen storage material
CN111569901A
Regulation and control method of cinnamyl aldehyde selective hydrogenation product catalyzed by carbon nitride loaded bimetallic
CN116713019A
Hydrogen storage by reversible hydrogenation of pi-conjugated substrates
US20040223907A1